Vasectomy as a Condition for Social Assistance: The Maqasid al-Shariah Approach and Gender Equality - Fitria, Mailiza; Firdaus, Beni; Rahmiati, Rahmiati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The policy proposal linking social assistance to vasectomy has sparked considerable debate due to its complex relationship with reproductive rights, ethical issues, and religious beliefs. This study addresses the topic through the framework of Maqasid al-Shari‘ah, focusing on two primary objectives: ḥifẓ al-nasl (protection of lineage) and hifz al-mal (protection of wealth), while also considering gender equality. Using a qualitative library research approach, the study explores a variety of sources related to Maqasid al-Shari‘ah, gender equality, population control, and the allocation of social welfare. The findings suggest that vasectomy is traditionally viewed as conflicting with ḥifẓ al-nasl because it directly impacts reproductive capacity. Reproductive decisions traditionally emphasize the preservation of lineage, and any action that impairs fertility is often seen as contrary to this objective. However, under the principle of necessity (ḍarūrah), there is room for exceptions, where actions like vasectomy may be justified if they lead to greater public welfare (maṣlaḥah), especially in cases of overpopulation or when the financial resources required for raising children exceed the capacity of families or the state. From a Maqasid perspective, vasectomy could contribute positively by improving the quality of future generations through more sustainable family planning. Additionally, involving men in contraceptive responsibility aligns with gender equality, fostering a more equitable distribution of reproductive duties between men and women. This approach promotes justice by reducing the disproportionate burden placed on women and encouraging shared responsibility in population control efforts, which are critical for maintaining the long-term effectiveness of social welfare programs.